PTU-141 Gastric Intestinal Metaplasia: A Retrospective Analysis In A District General Hospital In The United Kingdom. (9th June 2014) - Singanayagam, A; Chatrath, N; Pee, L; Loganayagam, A
Abstract : Introduction: Gastric intestinal metaplasia (IM) is part of a carcinogenesis sequence leading to gastric cancer. Recent evidence-based European Society of Gastrointestinal Endoscopy (ESGE) guidelines highlight additional risk factors, such as extensive intragastric distribution of IM and the presence of Helicobacter pylori . The former is identified with ≥2 antral and ≥2 corpus biopsies, involving the greater and lesser curvature, and warrants three-yearly surveillance endoscopies. The latter should be eradicated to slow carcinogenesis progression. Methods: Using keywords "intestinal metaplasia", the histology database for the Queen Elizabeth Hospital, South London, was reviewed over 2000–11 to identify patients with IM on gastric biopsy. Gastro-oesophageal junctional IM was excluded. The number and site of biopsies taken and the presence of H. pylori was identified. The terminology used, with regards to "extensive" and "focal" IM, was compared with the suggestions from the ESGE guidelines. To investigate the development of cancer in patients with IM, histology and upper gastrointestinal cancer databases were compared. Results: 175 patients with gastric IM were identified. Of these, only one patient developed gastric cancer. Helicobacter pylori was associated with 20/175 (11.4%) of gastric IM biopsies. After review of pathology reports, in 37/175 (21.1%) of cases with gastric IM, the pathologist did not receive sufficient clinical information specifying the site of the biopsies. Of those where the biopsy site was specified, only 10/138 (7.2%) had sufficient biopsies. The term "extensive" was used in 27/175 (15.4%) pathology reports, despite either insufficient number or non-specified location of biopsies. Conclusion: This study identified 175 patients with gastric intestinal metaplasia over 2000–2011. One patient developed gastric adenocarcinoma after 8 years. Since surveillance endoscopy is not routine practice in the Trust, all biopsies were incidental findings. This study suggests that, where biopsy site details were provided, only 7.2% of patients were adequately biopsied. Remaining cases should have repeat biopsies to decide on surveillance. "Extensive metaplasia" refers to a wide intragastric distribution of IM to include the antrum and corpus. We identified discrepant use of nomenclature in pathology reporting in 15.4%. Helicobacter pylori was associated in 11.4%, where ESGE advocates its eradication. This study reveals further work is needed to risk stratify and survey this important pre-cancerous condition. Reference: Dinis-Ribeiro M, Areia M, de Vries A, Marcos-Pinto R, Monteiro-Soares M, O'Connor A, et al . Management of precancerous conditions and lesions in the stomach (MAPS): guideline from the European Society of Gastrointestinal Endoscopy (ESGE). Endoscopy 2011 Dec 23;44(01):74–94 Disclosure of Interest: None Declared.